Clonal Glial Response in a Multiple Sclerosis Mouse Model - Bribian, Ana; Pérez-Cerdá, Fernando; Matute, Carlos; López-Mascaraque, Laura (Frontiers in Cellular Neuroscience, 2018)
Multiple sclerosis (MS) is an autoimmune disease causing central nervous system (CNS) demyelination and axonal injury. In the last years the importance of astrocytes in MS is rapidly increasing, recognizing astrocytes as highly active players in MS pathogenesis. Usually the role assigned to astrocytes in MS lesions has been the formation of the glial scar, but now their implication during lesion formation and the immune response increasingly recognized. Since astrocytes are a heterogeneous cell population with diverse roles in the CNS, the aim of this study was to analyze the putative clonal response of astrocytes in a demyelinating scenario. To undertake this aim, we used the induced experimental autoimmune encephalomyelitis (EAE) as a murine model for MS in previously electroporated mice with in vivo multicolor lineage tracing system, the StarTrack methodology. Our data revealed a variety of morphological changes that were different among distinct clones. In many cases, cells of the same clone responded equally to the injury, while in other cases clonally-related cells responded differently to the injury. Therefore, whereas some clones exhibited a strong morphological alteration, other clones located at similar distances to the lesion were apparently unresponsive. Thus, at present there is no compelling evidences that clonal relationship influences the position or function of astrocytes in the EAE model. Further, the coexistence of different astroglial clonal responses to the bran injury reveals the significance of development to determine the astrocyte features that respond to brain injuries.